2018
DOI: 10.1159/000493217
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Mechanisms of Myofibroblastic Activation: Outside-in and Inside-Out

Abstract: Myofibroblasts are central mediators of fibrosis. Typically derived from resident fibroblasts, myofibroblasts represent a heterogeneous population of cells that are principally defined by acquired contractile function and high synthetic ability to produce extracellular matrix (ECM). Current literature sheds new light on the critical role of ECM signaling coupled with mechanotransduction in driving myofibroblastic activation. In particular, transforming growth factor β1 (TGF-β1) and extra domain A containing fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 203 publications
0
72
0
Order By: Relevance
“…TGF-β1 signaling is crucial for the induction and maintenance of activated fibroblast phenotype through the Smad2/3 pathways 7,28 . In the present study, we found TNAP inhibition significantly suppressed the myofibroblast differentiation and collagen deposition both in post-MI hearts and in TGF-β1-treated CFs evidenced by the reducing expression of α-SMA, vimentin, collagen-related genes, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 signaling is crucial for the induction and maintenance of activated fibroblast phenotype through the Smad2/3 pathways 7,28 . In the present study, we found TNAP inhibition significantly suppressed the myofibroblast differentiation and collagen deposition both in post-MI hearts and in TGF-β1-treated CFs evidenced by the reducing expression of α-SMA, vimentin, collagen-related genes, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…It had been demonstrated previously that the ECM is an important regulator of myofibroblast activation [32]. Notably, a fibrotic ECM scaffold was shown to lead to activation of control fibroblasts, while conversely, plating of activated myofibroblasts derived from IPF patients onto an ECM scaffold from control lungs resulted into a quiescent phenotype similar to control fibroblasts, suggesting that ECM is a prominent determinant that dictates fibroblast activation [33].…”
Section: Fig 6 Evaluation Of Epithelial and Mesenchymal Gene Expressmentioning
confidence: 94%
“…Therapeutically, blockade of the renin-angiotensin II (Ang II)-aldosterone system by angiotensin converting enzyme (ACE) inhibitors or angiotensin II-type1 receptor antagonists can slow down fibrosis [1], but it is not yet possible to halt or reverse fibrosis. Cardiac fibrosis is driven by myofibroblasts, which arise mainly from transdifferentiation of resident cardiac fibroblasts after exposure to mediators like Ang II and transforming growth factor-β as well as in response to altered biomechanical properties of their surroundings [2][3][4][5]. Understanding the molecular events underlying fibrosis is essential to identify new therapeutic antifibrotic strategies for the treatment of heart failure.…”
Section: Introductionmentioning
confidence: 99%